A description of the genus Denitromonas nom. rev.: Denitromonas iodatirespirans sp. nov., a novel iodate-reducing bacterium, and two novel perchlorate-reducing bacteria, Denitromonas halophila and Denitromonas ohlonensis, isolated from San Francisco Bay intertidal mudflats - Victor M. Reyes-Umana; John D. Coates (Microbiology Spectrum, 2023)
ABSTRACT The genus Denitromonas is currently a non-validated taxon that has been identified in several recent publications as members of microbial communities arising from marine environments. Very little is known about the biology of Denitromonas spp., and no pure cultures are presently found in any culture collections. The current epitaph of Denitromonas was given to the organism under the assumption that all members of this genus are denitrifying bacteria. This study performs phenotypic and genomic analyses on three new Denitromonas spp. isolated from tidal mudflats in the San Francisco Bay. We demonstrate that Denitromonas spp. are indeed all facultative denitrifying bacteria that utilize a variety of carbon sources such as acetate, lactate, and succinate. In addition, individual strains also use the esoteric electron acceptors perchlorate, chlorate, and iodate. Both 16S and Rps/Rpl phylogenetic analyses place Denitromonas spp. as a deep branching clade in the family Zoogloeaceae, separate from either Thauera spp., Azoarcus spp., or Aromatoleum spp. Genome sequencing reveals a G + C content ranging from 63.72% to 66.54%, and genome sizes range between 4.39 and 5.18 Mb. Genes for salt tolerance and denitrification are distinguishing features that separate Denitromonas spp. from the closely related Azoarcus and Aromatoleum genera. IMPORTANCE The genus Denitromonas is currently a non-validated taxon that has been identified in several recent publications as members of microbial communities arising from marine environments. Very little is known about the biology of Denitromonas spp., and no pure cultures are presently found in any culture collections. The current epitaph of Denitromonas was given to the organism under the assumption that all members of this genus are denitrifying bacteria. This study performs phenotypic and genomic analyses on three Denitromonas spp., Denitromonas iodatirespirans sp. nov.—a novel iodate-reducing bacterium—and two novel perchlorate-reducing bacteria, Denitromonas halophila and Denitromonas ohlonensis, isolated from San Francisco Bay intertidal mudflats.